Theoretical study on rhombohedral domain and associated properties in perovskite ferroelectric materials - Huang, Chuanwei. (2013)
Ferroelectric materials have attracted considerable attention due to their novel physical properties and plenty of potential applications in electronic devices, such as sensors, actuators, and non-volatile random access memories. As the main distinctive features in ferroelectrics, equilibrium domain structure and its transformation, which are vital to the properties and potential applications, are highly sensitive to various external electrical and mechanical boundary conditions. In the present thesis, we investigated the external influences, incorporating both depolarization field and misfit strain, on the stability of rhombohedral domain patterns, domain size, phase transition, and associated dielectric/piezoelectric properties of perovskite ferroelectric films. A comprehensive theoretical analysis on the effect of depolarization field on rhombohedral ferroelectric films has been addressed in this dissertation. It has been demonstrated that the depolarization field significantly influences the formation and transformation of rhombohedral domains in (001) epitaxial ferroelectric films. The stable domain pattern of rhombohedral films changes from 109° to 71° with the reduction of the residual depolarization field. This result indicates a possibility of manipulation of 71° and 109° domains reliably by controlling the electrical boundary condition on surfaces of the ferroelectric films. We extended to investigate the effect of depolarization field on domain size. The effect of the depolarization field on rhombohedral ferroelectric films could reconcile the paradox of domain size scaling behavior between the experimentally observed results and the pure elastic predictions. Furthermore, analogies and differences in domain size scaling behaviors between rhombohedral ferroelectric and ferroelastic films were analyzed. The results imply that there is a general thickness-dependent domain size scaling behavior for ferroic films, including: (I) the classical ½ power law relationship for thick films, (II) the deviation from the ½ relationship for intermediate film thickness and (III) an increase exponentially in ultrathin films when decreasing the film thickness.